The Quality of Services Provided by The Extension Farm to Vegetable Farmers in Al-Rashidiya District/Baghdad Governorate - Ihsan Radhi Hassuny (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2026)
The study aimed to assess the quality of services provided by the extension farm for vegetable farmers in the Rashidiya District, Baghdad Governorate, as well as identifying the problems vegetable farmers face in accessing the services provided by the extension farm. The study population included all vegetable farmers in the Rashidiya District, Baghdad Governorate, who are members of farmers’ associations, totaling 2,693 farmers. A random sample of 4% (108 farmers) was selected from this group. Data were collected from the respondents using a questionnaire and through face-to-face interviews during the period from January 15, 2026, to February 27, 2026. The research results concluded that all dimensions comprising the quality of services provided by the extension farm achieved an average quality level, with an overall arithmetic mean of 1.43 points, and a standard deviation of 1.04 points .The most significant issue identified was that recommendations regarding vegetable crops were not received in a timely manner, ranking first in importance with a weighted mean of 2 points. Conversely, the lack of incentives to participate in training programs ranked last. with a weighted mean of 1.73 points, The researcher recommended increasing the number of staff at the extension farm and enhancing their expertise, as well as utilizing modern communication methods and information technology to expedite the delivery of recommendations and information to vegetable farmers, thereby closing the existing service gap and elevating the overall quality of extension services from an average to an excellent level.